2012
DOI: 10.1002/em.21692
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic responses following maternal dietary exposure to physiologically relevant levels of bisphenol A

Abstract: Animal studies have linked perinatal bisphenol A (BPA) exposure to altered DNA methylation, but little attention is given to analyzing multiple physiologically relevant doses. Utilizing the viable yellow agouti (Avy) mouse, we examine the effects of developmental exposure through maternal diet to 50 ng BPA/kg (n = 14 litters), 50 μg BPA/kg (n = 9 litters), or 50 mg BPA/kg (n = 13 litters) on global and candidate gene methylation at postnatal day 22. Global methylation analysis reveals hypermethylation in tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 42 publications
8
123
1
1
Order By: Relevance
“…Though the induced shift is small, multiple studies have shown correlations with small absolute methylation shifts in transposons are associated with human aging and exposure to air pollution. 20,31,32 Imprinted genes are often used as candidate loci for environmentally induced epigenetic change, making a study of their natural change in DNA methylation over the life-course a valuable baseline measurement. 33,34 For example, human insulin-like growth factor 2 (IGF2) DNA methylation has been positively correlated with age in multiple cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the induced shift is small, multiple studies have shown correlations with small absolute methylation shifts in transposons are associated with human aging and exposure to air pollution. 20,31,32 Imprinted genes are often used as candidate loci for environmentally induced epigenetic change, making a study of their natural change in DNA methylation over the life-course a valuable baseline measurement. 33,34 For example, human insulin-like growth factor 2 (IGF2) DNA methylation has been positively correlated with age in multiple cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Imprinted genes contain parent-of-origin epigenetic marks, including differentially methylated regions (DMRs), resulting in mono-allelic expression. These commonly used biomarkers host CpG islands that are variably methylated 19 or differentially methylated, 18,20 respectively, and environmental exposures have been shown to stably influence their epigenetic marks and subsequent gene expression. [21][22][23][24] Therefore, measuring the relative change in DNA methylation from early to adult life in epigenetically labile regions is crucial to determining whether early life Pb exposure can alter the magnitude or direction of epigenetic drift.…”
Section: Introductionmentioning
confidence: 99%
“…42 For example, total liver BPA measurements in animals fed the highest dose of BPA, 50 mg/kg chow, ranged from 9.5 to 870 mg/kg liver, which encompasses the maximum human environmental exposure indicated by human fetal liver measurements, ranging from below the limit of quantitation (LOQ) to 96.8 mg BPA/kg liver. 42 Anderson et al 42 reported BPA concentrations of < LOQ-11.3 mg/kg liver (mean 2 mg/ kg; median 0.6 mg/kg) and < LOQ-13 mg/kg liver (mean 2.8 mg/kg; median 0.3 mg/kg) in livers from mice fed diets containing BPA at 50 mg/kg chow and 50 ng/kg chow, respectively. 3 This mating scheme produced approximately 50% wild type (a/a) offspring and approximately 50% heterozygous (A vy /a) offspring.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of A vy /a mice were euthanized on post-natal day (PND) 22. 32 A subset of wild type (a/a) mice (approximately 1 male and 1 female per litter for each BPA diet group) were then housed with a same-sex A vy /a sibling and fed the standard phytoestrogen-free control diet until they were euthanized at 10 months of age, as described by Anderson et al (Table 1). 50 During dissection of both PND22 and 10-month animals, liver tissue was collected and flash frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation